Effects of endogenous levels of master regulator PrgX and peptide pheromones on inducibility of conjugation in the enterococcal pCF10 system. - Erickson, Rebecca J B (Mol Microbiol, 2019)
Enterococcal pheromone responsive conjugative plasmids like pCF10 promote horizontal spread of antibiotic resistance genes following induction of plasmid-containing cells by potential recipients. Transcription of conjugation genes from promoter P(Q) is inhibited by the master regulator PrgX, further repressed when PrgX is in complex with the inhibitory I peptide, and allowed when PrgX is in complex with the C inducing peptide. Single cell analysis has shown that heterogeneity in the pheromone response is prevalent. Here, we systematically varied levels of regulatory molecules to better understand why some individual cells have increased propensity for induction. In this study, PrgX was confirmed to repress P(Q) in the absence of exogenous peptides in vivo, but cells with increased levels of PrgX were shown to be more prone to induction. Further, ablation of endogenous I reduced PrgX levels, resulting in reduced basal repression and loss of inducibility. Reduction of both endogenous peptides by washing increased the inducibility of cells. Together, these results show that endogenous PrgX, C, and I levels can impact the induction potential of a cell and establish the importance of basal I for regulation. These results also suggest that PrgX/C complexes may directly activate prgQ transcription, contrary to a long-standing working model.